Herbicides in surface water bodies - behaviour, effects on aquatic organisms and risk assessment - Stevanovic, Marija; Gašić, Slavica (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2020)
Pesticides play a very important role in reducing losses and maintaining quality in cropproduction. Although positive effects of pesticide use are undeniable, adverse effectsare frequent. This has led to a comprehensive reevaluation of the benefits of pesticideuse and potential adverse effects on human health and the environment before placingthem on the market. The fact that pesticides are designed to be toxic and are deliberatelyintroduced into the environment, makes them a very important and strictly regulatedgroup of pollutants. The most commonly used group of pesticides are herbicides, andtheir detection in surface water bodies has been repeatedly reported. In spite of beingdesigned to be toxic to target species, adverse effects on other inhabitants of aquaticenvironments have also been observed. In order to prevent negative environmental effects,the registration process for active substances and plant protection products involvespredictive environmental risk assessments (ERA). Reliable assessment of long-term effectson non-target species, natural populations and ecosystems is a priority and ERA processis constantly being improved.
Keywords: herbicides; water; aquatic organisms; toxicity; risk assessment